Randomized Controlled Trial of Light Therapy for Fatigue Following Traumatic Brain Injury. (May 2014) - Sinclair, Kelly L.; Ponsford, Jennie L.; Taffe, John; Lockley, Steven W.; Rajaratnam, Shantha M. W.
Background . Fatigue is a common, persistent complaint following traumatic brain injury (TBI). Effective treatment is not well established. Objective . The current study aimed to investigate the efficacy of 4 weeks of light therapy for fatigue in patients with TBI. Methods . We undertook a randomized, placebo-controlled study of 4-week, 45 min/morning, home-based treatment with short wavelength (blue) light therapy (λmax = 465 nm, 84.8 µW/cm 2, 39.5 lux, 1.74 × 10 14 photons/cm 2 /s) compared with yellow light therapy (λmax = 574 nm, 18.5 µW/cm 2, 68 lux, 1.21 × 10 12 photons/cm 2 /s) containing less photons in the short wavelength range and a no treatment control group (n = 10 per group) in patients with TBI who self-reported fatigue and/or sleep disturbance. Assessments of fatigue and secondary outcomes (self-reported daytime sleepiness, depression, sleep quality, and sustained attention) were conducted over 10 weeks at baseline (week −2), midway through and at the end of light therapy (weeks 2 and 4), and 4 weeks following cessation of light therapy (week 8). Results . After controlling age, gender, and baseline depression, treatment with high-intensity blue light therapy resulted in reduced fatigue and daytime sleepiness during the treatment phase, with evidence of a trend toward baseline levels 4 weeks after treatment cessation. These changes were not observed with lower-intensity yellow light therapy or no treatment control conditions. There was also no significant treatment effect observed for self-reported depression or psychomotor vigilance performance. Conclusions . Blue light therapy appears to be effective in alleviating fatigue and daytime sleepiness following TBI and may offer a noninvasive, safe, and nonpharmacological alternative to current treatments.